Core microbiota for nutrient digestion remained and ammonia utilization increased after continuous batch culture of rumen microbiota in vitro - Liu, Mengyu; Wang, Tong; Wang, Lu; Xiao, Hanjie; Li, Jinhui; Duan, Chunhui; Gao, Lijie; Liu, Yueqin; Yan, Hui; Zhang, Yingjie; Ji, Shoukun (Frontiers in Microbiology, 2024)
Introduction: This study aimed to investigate the digestive function, urea utilization ability, and bacterial composition changes of rumen microbiota under high urea (5% urea in diet) over 23 days of continuous batch culture in vitro. Methods: The gas production, dry matter digestibility, and bacterial counts were determined for the continuously batch-cultured rumen fluid (CRF). The changes in fermentation parameters, NH3-N utilization efficiency, and microbial taxa were analyzed in CRF and were compared with that of fresh rumen fluid (RF), frozen rumen fluid (FRF, frozen rumen fluid at -80℃ for one month), and the mixed rumen fluid (MRF, 3/4 RF mixed with 1/4 CRF) with in vitro rumen fermentation. Results: The results showed that the dry matter digestibility remained stable while both the microbial counts and diversity significantly decreased over the 23 days of continuous batch culture. However, the NH3-N utilization efficiency of the CRF group was significantly higher than that of RF, FRF, and MRF groups (P<0.05), while five core genera including Succinivibrio, Prevotella, Streptococcus, F082, and Megasphaera were retained after 23 days of continuous batch-culture. The NH3-N Utilization efficiency was effectively improved after continuous batch-culture in vitro, and Streptococcus, Succinivibrio, Clostridium_sensu_stricto_1, p.251.o5, Oxalobacter, Bacteroidales_UCG.001, and p.1088.a5_gut_group were identified to explain 75.72% of the variation in NH3-N utilization efficiency with RandomForest model. Conclusion: Thus, core bacterial composition and function retained under high urea (5% urea in diet) over 23 days of continuous batch-culture in vitro, and bacterial biomarkers for ammonia utilization were illustrated in this study. These findings might provide potential applications in improving the efficiency and safety of non-protein nitrogen utilization in ruminants.